Congenital right diaphragmatic defects: Our institutional experience - Jayalaxmi Shripati Aihole (Wolters Kluwer Medknow Publications, 2021)
Background: The descriptive clinical study was conducted to analyse the clinical profile as well as the outcome of congenital right diaphragmatic defects among children including neonates in a tertiary care referral neonatal and paediatric centre in southern Karnataka, India. Materials and Methods: This retrospective and prospective observational clinical study was conducted from January 2005 to August 2019, over a period of 14.7 years in a tertiary care referral neonatal and paediatric centre. Clinical characteristics and risk factors of 33 children including neonates admitted and diagnosed with congenital right diaphragmatic defects were assessed both pre- and postoperatively. Neonates and children with acquired right diaphragmatic hernia defects and the left-sided diaphragmatic defects were not included in this clinical study. Results: For statistical as well as clinical analysis, 33 study subjects were grouped into four groups, depending on the pre-operative and intraoperative findings as well as on their final diagnosis. Group I comprised right congenital diaphragmatic hernia (RCDH) (n = 18), Group II comprised RCDH with sac (n = 6), the babies with diagnosis of right diaphragmatic eventration were included in Group III (n = 7), whereas babies with other right-sided diaphragmatic hernia defects diagnosis were included in Group IV (n = 2). Conclusion: Right-sided congenital diaphragmatic defects, though rare, do carry excellent survival if referred early and managed in a tertiary care neonatal and paediatric centre as that of left diaphragmatic defects.